Reinventing ITIL® in the Age of DevOps Innovative Techniques to Make Processes Agile and Relevant - Krishna Kaiser, Abhinav (Apress, 2018)
Delve into the principles of ITIL and DevOps and examine the similarities and differences. This book re-engineers the ITIL framework to work in DevOps projects without changing its meaning and its original objectives, making it fit for purpose for use in DevOps projects. Reinventing ITIL in the Age of DevOps shows you the relevance of ITIL since the emergence of DevOps and puts a unique spin on the ITIL service management framework. Along the way you will see that ITIL is a mature service management framework and years of maturity will be lost if it's made invalid. The ideas, recommendations, and solutions provided in Reinventing ITIL in the Age of DevOps can be leveraged in order to readily develop solutions or create proposals for clients. The ideas in this book can be further expanded to deliver seamless services to DevOps projects. You will: • Discover the basics of ITIL and DevOps • Compare ITIL and DevOps • Understand the structure of a DevOps organization and adapt the ITIL roles to this structure • Re-engineer ITIL for DevOps projects • Implement major processes such as incident management, configuration management, and change management processes in DevOps projects • Automate activities within processes.